The umbrella lady - Andrews, V. C. (Virginia C.) (Pocket Books, 2022)
Left on the train platform of some strange village, eight-year-old Saffron Faith Anders is certain her father will return shortly, just like he promised. She holds out hope as the hour grows late and the station sets to close. She clings to her suitcase like a life raft. When a peculiar old woman carrying a large umbrella approaches and inquires about her situation, Saffron doesn't immediately trust the imposing do-gooder, but eventually does agree to rest at her house while they wait for her father together. Saffron's stay was supposed to be for a few minutes, hours at most. But confined to a house not unlike one Hansel and Gretel might have encountered, Saffron will undergo months--and then years--of transformation at the hands of the Umbrella Lady. One minute grandmotherly and the next a scolding schoolmarm, the woman cuts Saffron's hair to the nub, burns the clothes in her suitcase, and pretends that the photo of a young girl hanging on her bedroom wall is just a stock image that came with the frame. When mysterious letters arrive from Saffron's father, saying he has started a new family and will send for her shortly, hope returns to her heart. Still, as is the fate of all young protagonists in the world of V.C. Andrews, Saffron will learn that those who most claim to care for you will often hurt you the worst...